THE ROLE OF THE SECONDARY MARKET (TRADING) IN THE DEVELOPMENT OF LOCAL SAVINGS IN IRAQ FOR THE PERIOD (2004-2020) - Yousif Abdullah Al- Ani; Haneen Salim Al-Obaidi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
The stock markets, in general, have become an effective tool for direct financing of investments and economic development projects, as it works to bridge the financing gap in the economy by mobilizing resources from surplus units to deficit units. Providing capital gains from buying and selling securities in these markets. The research aims to study and analyze the role of the secondary market in Iraq in the development of local savings for the period (2004-2020), and to know the amount of savings that the market has managed to attract and direct towards investment compared to local savings and other financial institutions, especially banks. The descriptive analytical method has been used for the performance indicators of the Iraq Stock Exchange. The results showed the weakness of the relative absorptive capacity of the secondary market, as well as the existence of a large gap between the volume of funds destined to invest in securities in the secondary market and the volume of funds used as deposits in the Iraqi banking system during the research period. The researcher recommended giving priority to the Iraqi market for securities in mobilizing savings and directing them towards investment and then contributing to the implementation of economic policies to ensure the activity of the secondary market.